Guest Editorial Vol2 no2 - Kirstie Maclean (Scottish Journal of Residential Child Care)
After just over 3 years as Director of the Scottish Institute for Residential Child Care (SIRCC), I am returning to work in the Social Work Services Inspectorate. This has caused me to reflect on whether anything has changed in residential care over that period and, if so, what and why. It is my conviction that there has been change, although much of the change is quite small, gradual and, to some extent, fragile. Nevertheless, it leads me to believe that a corner has been turned. The old side of the corner often had residential care viewed as in decline and a last resort; the new side of the corner has residential child care increasingly seen as a positive choice for some children and young people and a valued part of the placement spectrum.